Penerapan Metode Storytelling Islami Dalam Menanamkan Nilai Pemaaf Dan Pengampun Dari Asmaul Husna Al’afuww Dan Al-ghaffar - Alia Aqila (EL-EMIR Institute, 2025)
This study aims to describe the application of the Islamic storytelling method as an alternative learning method to instill the values ​​of forgiveness and forgivingness derived from the Asmaul Husana Al-'Afuww and Al-Ghaffar. The method used was classroom action research (CAR) with a qualitative descriptive approach. The subjects were 20 12th-grade students of Al-Manar High School, Medan. Data were collected through observation, tests, interviews, documentation, and field notes, then analyzed qualitatively and quantitatively. The results showed that the application of the Islamic storytelling method can improve students' understanding of memorizing and interpreting the Asmaul Husana, while simultaneously fostering an attitude of forgiveness and forgivingness in everyday life. Furthermore, this method has been proven to make the learning process more engaging, interactive, and memorable. Therefore, Islamic storytelling can be used as an alternative learning strategy to improve the quality of Aqidah Akhlak (belief and morals) learning while strengthening students' spiritual values.